DESIGNING A GREEN INDUSTRY BUSINESS MODEL WITH AN APPROACH ITERATIVE PROCESS MODEL DIAGRAM IN THE REGIONAL LEADERSHIP OF 'AISYIYAH BALI' - Erna Trisnawati; Yulianto Umar Rofii; Bayu Wardhana (ECOBISMA (JURNAL EKONOMI, BISNIS DAN MANAJEMEN), 2026)
PURPOSE - Study this done with objective For designing business models and integrating green industry principles with Iterative Process Model Diagram approach.METHODOLOGY - Design This made with objective For create mark circular economy for the community with still notice values sustainability for environment . In planning This using the Iterative Process Model Diagram model which enables the business model design process done in a way evaluative and adaptive stages . The study was conducted on fostered MSMEs through The Economic and Manpower Council of the Regional Leadership of ' Aisyiyah Bali' which has potential For implement practice friendly environment . This research uses a qualitative approach qualitative descriptive approach that combines the Iterative Process Model Diagram method. qualitative descriptive used to design , develop , and test industrial business models green.FINDING - Have feedback from each cycle testing enables the Iterative Process Model method, which uses a development model gradual and repetitive . Research results produce business model concept with notice practice friendly environment . Research This recommend a sustainable business model that emphasizes to circularity production , utilization waste trash and collaboration between party.